Local adaptation of a bacterium is as important as its presence in structuring a natural microbial community - Pedro Gómez (Nature Portfolio, 2016)
Though both the presence and traits of a species can influence the dynamics of its ecological community, the effects of these factors are difficult to disentangle. Here, Gómez et al. demonstrate in a microbial mesocosm that local adaptation of a focal species can influence the community as much as the presence of the focal species per se.